Younger tamoxifen-treated breast cancer patients also had higher risk of endometrial cancer and the risk could be reduced by sequenced aromatase inhibitor use: A population-based study in Taiwan - Sung-Chao Chu; Chia-Jung Hsieh; Tso-Fu Wang; Mun-Kun Hong; Tang-Yuan Chu (Tzu Chi Medical Journal)
Objective: Previous Western studies reported that older (≥50 years) breast cancer survivors with tamoxifen treatment had higher risk of endometrial cancer. This study aims to disclose whether younger (<50 years) tamoxifen-treated breast cancer patients also had higher risk of endometrial cancer and to examine whether sequenced aromatase inhibitor (AI) use could reduce the risk. Materials and Methods: A population-based cohort of 39,216 newly diagnosed breast cancer patients was identified from Taiwan National Health Insurance Database from 1999 to 2012. The risk of endometrial cancer in nonusers (n = 14,588), tamoxifen-only (n = 19,302), and sequenced AI (n = 5326) users was compared with Cox regression analysis and was adjusted with age, diabetes, hypertension, and chemotherapy. Results: During the 14-year study period, 133 patients were diagnosed with subsequent endometrial cancers. Compared with nonusers, tamoxifen-only users had higher risk of endometrial cancer (14-year incidence 1.7% vs. 0.3%; adjusted hazard ratio [HR] 3.90; 95% confidence interval [CI], 2.37–6.42). This was observed in both older (≥50 years) and younger (40–50 years) age groups. Adjusted HR (95% CI) for the latter was 3.74 (1.65–8.48). This risk persisted after cessation of tamoxifen use. The risk of endometrial cancer was lower in sequenced AI when compared with tamoxifen-only users (adjusted HR 0.43; 95% CI, 0.25–0.72). Conclusions: Not only patients ≥50 years but also younger (40–49 years) patients with tamoxifen treatment had higher risk of subsequent endometrial cancer in this nation-wide cohort. We suggest regular gynecologic monitoring not only during active use but also during follow-up phase. Sequenced AI use may reduce the risk of endometrial cancer in tamoxifen-treated breast cancer patients.